Diversified Bund Vegetation Coupled With Flowering Plants Enhances Predator Population and Early-Season Pest Control. Issue 4 (14th April 2021) - Qian, Ping; Bai, Yueliang; Zhou, Wenwu; Yu, Hang; Zhu, Zijie; Wang, Guiyao; Quais, Md Khairul; Li, Feiqiang; Chen, Yue; Tan, Ye; Shi, Xiaoxiao; Wang, Xueqin; et al.
Abstract: Insecticide overuse in crop production systems often results in detrimental effects on predators and parasitoids, which regulate important insect pests. The natural enemies are also unable to survive in monocrop landscapes with the absence of shelter or food sources. Diversified vegetation, especially with flowering plants, can enhance natural enemy abundance and diversity, thus strengthening biological control, enabling farmers to reduce insecticides. In this study, we conserved bund vegetation and manipulated the existing rice landscapes with flowering plants to provide food and shelter for the biological control agents. Our study revealed significant positive relationships between predator densities and bund plant diversity. The abundance of predators significantly increased in the eco-engineered plots, especially at the flowering peaks compared to the insecticide-treated and control plots, while parasitoids were more diverse in both the eco-engineered and control plots. There were no significant differences in planthopper and leafhopper densities among the treatments during the rice early and maximum tillering stages, suggesting effective natural control of these herbivore pests in the eco-engineered plots at the early rice-growing season. However, at the heading stage relatively higher planthopper and leafhopper populations in the control and eco-engineered plots than in the insecticide-sprayed plots were recorded, suggesting perhaps the need for insecticide interventions if exceeding the threshold at this time. Our study indicates that manipulating the habitats surrounding the rice fields to enhance natural enemies is a sustainable practice in rice production as it can enhance the natural suppression of pests and thus reducing the need for insecticide.